KAIZEN: The Key to Japan’s Competitive Success - อรุณรัศมีเรือง ศักชัย (Business Administration and Management Journal Review, 2013)
This article has introduced the Japanese industrial management that are recognized as world class manufacturer especially for an adopted Japanese way so called “ KAIZEN ” in the philosophy meaning of continuous improvement or continual improvement. Some scholar uses in Thai as improvement without ending. In general, this concept always look forward to getting a better ways by believing that “ No Best Way at All ” Everything can be continuously improved. Furthermore the key for KAIZEN would be operators who are core people for driving the activities successfully (Bottom up). Management would give advices and right direction, including motivation their people to implement and work altogether for the pursuit of organization’s goal. The philosophy of KAIZEN is the operations management of Japanese industry whose success does not only come from the innovation but their culture of KAIZEN. This has been implanted into self learning started from learning in family, as well as in educational institutes through awareness, practices and enthusiasm. It is the most important base for building the quality of people influenced to the greatness of Japanese industry as present.